Effect of Dietary Supplementation of a Feed Additive Rich in Polyphenols in Growth, Hepatic lipogenesis and Gut Microbiota in Atlantic Salmon (Salmo salar) Fed a High-Carbohydrate Diet - Villasante - Urquiza, Alejandro (2018)
FONDECYT de Postdoctorado 2016 Proyectos de Investigación Polyphenols gut microbiota feed additive Nutrición Molecular En Peces Fisiología De Peces Reproducción Proyectos de Investigación Finalizado